Novejša sodna praksa SEU o diskriminaciji na podlagi spola - Kresal, Barbara (Podjetje in delo, 2015)
Prohibition of discrimination based on sex is one of the fundamental principles of EU law. The Court of Justice of the European Union (CJEU) has developed a rich case-law in relation to this issue. The article analyses cases from the resent case-law of the CJEU dealing with this issue which address, for instance, the question of equal access to employment and promotion without any less favourable treatment related to pregnancy or maternity leave. Furthermore, it also analyses the question of the right to return to the same or equivalent post after the expiry of parental leave, the question of equal pay in relation to the taking into account the taking care for children for the purposes of acquiring old-age pension and its calculation. The article also presents the CJEU case-law on the question of equal compensation for long-term disability without any discrimination based on sex, the issue of maternity leave in the case of surrogacy arrangements, and some other questions.
Keywords: človekove pravice; human rights; kršenje; spolna diskriminacija